The Role of Key Audit Matters as a Means of Communication between Auditors and Users of Financial Statements: Peran Key Audit Matters sebagai Alat Komunikasi Auditor dengan Pengguna Laporan Keuangan - Yunita Anggraini Setyawati; Acynthia Ayu Wilasittha (Jurnal Akuntansi, Keuangan dan Perpajakan, 2026)
This study has the main objective to examine in depth and comprehensively the role of key audit matters (KAM) as an important means of communication between auditors and users of financial statements, guided by the International Standard on Auditing (ISA) 701 on Communicating Key Audit Matters in Independent Auditor's Reports. The research method used is a Systematic Literature Review (SLR) with a qualitative approach, which is compiled based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search process was carried out through the Google Scholar and ScienceDirect databases, from 120 articles obtained 10 relevant articles from Scopus accredited international journals that specifically discuss the disclosure of KAM in independent auditor reports. Based on the results of the study, it was found that the disclosure of KAM functions as a communication tool that can increase transparency and deepen the understanding of financial statement users of significant risks faced by the audited entity, while providing an overview of the audit focus and the complexity of the examination faced by the auditor, thus potentially reducing information asymmetry and the audit expectation gap between auditors and stakeholders. However, its effectiveness depends heavily on the quality of disclosure, user characteristics, and the institutional and cultural environment in which KAM is implemented.   AbstrakPenelitian ini memiliki tujuan utama untuk mengkaji secara mendalam dan komprehensif mengenai peran key audit matters (KAM) sebagai salah satu sarana komunikasi yang penting antara auditor dengan pengguna laporan keuangan, dengan berpedoman pada International Standard on Auditing (ISA) 701 tentang Pengomunikasian Key Audit Matters dalam Laporan Auditor Independen. Metode penelitian yang digunakan adalah systematic literature review (SLR) dengan pendekatan kualitatif, yang disusun berdasarkan pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Proses penelusuran literatur dilakukan melalui basis data Google Scholar dan ScienceDirect, dari 120 artikel diperoleh 10 artikel relevan dari jurnal Internasional terakreditasi Scopus yang secara khusus membahas mengenai pengungkapan KAM dalam laporan auditor independen. Berdasarkan hasil kajian, ditemukan bahwa pengungkapan KAM berfungsi sebagai alat komunikasi yang mampu meningkatkan transparansi serta memperdalam pemahaman pengguna laporan keuangan terhadap risiko-risiko signifikan yang dihadapi entitas yang diaudit, sekaligus memberikan gambaran mengenai fokus audit dan kompleksitas pemeriksaan yang dihadapi auditor, sehingga berpotensi mengurangi asimetri informasi dan audit expectation gap antara auditor dan pemangku kepentingan. Namun demikian, efektivitasnya sangat bergantung pada kualitas pengungkapan, karakteristik pengguna, serta lingkungan institusional dan budaya tempat KAM diterapkan.